Fostering Youth-Led ASEAN Interest Group in South Korean Universities: Preliminary Studies of Two ASEAN Roundtables - Qobulsyah, Mochamad Alvin Dwiana; Darmawan, Frederica Christie; Dewi, Anggia Utami (Universitas Gadjah Mada, 2025)
During the COVID-19 pandemics, most of the youth's extracurricular events and activities in South Korean universities had been halted. These included the student-led interest group that was purposed to promote better understanding and people-to-people connections from South Korea and other regions, including the Southeast Asia region and the ASEAN organization. This paper aims to provide initial insights into how these student-led ASEAN Interest Groups show their eagerness to survive the pandemic semesters and keep their existence as a common and sustainable space for youth in South Korean universities better to understand the Southeast Asia region and its people. As a preliminary case study, this research conducted mini field research observation on-site and virtually in two ASEAN roundtable groups in two South Korean universities for two months (mid-September 2021 to early November 2021). These activities include participating in both groups' regular meetings, monitoring social network service (SNS/social media) accounts, disseminating voluntary primary demographic and aspirations surveys for the groups' members, and in-depth interviews with the groups' in-office and former coordinators. The result from this mini-ethnographic study later deliberated into how these student-led ASEAN interest groups in South Korean universities can play a role in lime lighting a young, dynamic, and prospective region of Southeast Asia amongst young Koreans that still have a limited understanding of the Southeast Asia region and culture, that in the future can play in building a sustainable and future-oriented ASEAN-South Korea partnership.